Editions-hymns of 1861 - Gargasaitė, Dalia (Knygotyra, 1980)
Before the rebellion of 1863 in Poland, Lithuania, Byelorussia took place a lot of manifestations, which were held in the streets, in churches and so on. During the demonstrations people sang hymns „Boże, coś Polskȩ...”, „Jeszcze Polska nie zginȩła...” and others, which later on were called in literature national hymns of Poles. These hymns had traces of politics, called to the fight against tsarism, carried the ideas of Lublin unia. These hymns became popular among different peoples – they were translated into Russian, Latvian, Byelorussian, Ukrainian, Lithuanian languages. The year of edition of the „Giesmės nabožnos” was unknown: Now the year of edition is defined – 1861. It was founded by soviet historian A. F. Smirnov that the Polish hymn „Boże, coś Polskȩ...” was translated into Lithuanian by the student of the Petersburg university T. Nešukaitis. In the article is suggested supposition that hit translation was published in the edition „Giesmės nabožnos” and new facts of his biography are throwlighted upon. There are some other translations of this hymn into Lithuanian, but the authors are unknown. The other Polish hymn „Jeszcze Polska nie zginȩła...” was translated into Lithuanian for some times. This hymn was very popular among the people. In this article also are published new facts of its translator’s K. Siaurimavičius’s biography.